Workshop on Nanotechnology 2011/1 "Understanding DNA Biomolecule for Lab-On-Chip Application" - Nor Azah, Yusof, Prof. Madya Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Institute of Nano Electronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th June 2011 at Seminar Room Tun Za'ba, Unit Kesihatan & Keselamatan Pekerjaan, Seriab Campus, Perlis, Malaysia.